2018
DOI: 10.1208/s12248-018-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

PBPK and its Virtual Populations: the Impact of Physiology on Pediatric Pharmacokinetic Predictions of Tramadol

Abstract: In pediatric PBPK models, age-related changes in the body are known to occur. Given the sparsity of and the variability associated with relevant physiological parameters, different PBPK software providers may vary in their system's data. In this work, three commercially available PBPK software packages (PK-Sim®, Simcyp®, and Gastroplus®) were investigated regarding their differences in system-related information, possibly affecting clearance prediction. Three retrograde PBPK clearance models were set up to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
2
25
0
1
Order By: Relevance
“…After intravenous administration, tramadol is rapidly distributed and metabolized. Approximately 20% of tramadol is cleared by the kidney, and the rest is cleared by liver metabolism 10 . Previous studies have demonstrated that tramadol is metabolized in the liver mainly by CYP2D6 (O‐desmethyl tramadol—M1), CYP3A4 (N‐desmethyl tramadol—M2), and CYP2B6 (N‐desmethyl tramadol—M2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After intravenous administration, tramadol is rapidly distributed and metabolized. Approximately 20% of tramadol is cleared by the kidney, and the rest is cleared by liver metabolism 10 . Previous studies have demonstrated that tramadol is metabolized in the liver mainly by CYP2D6 (O‐desmethyl tramadol—M1), CYP3A4 (N‐desmethyl tramadol—M2), and CYP2B6 (N‐desmethyl tramadol—M2).…”
Section: Methodsmentioning
confidence: 99%
“…The CYP2D6 contribution represented 43% of the hepatic clearance as previously described, the CYP2B6 contribution was determined as 10% of the hepatic clearance, and the remaining CYP3A4 contribution was 47% 10,11 . Therefore, we set f m, CYP2D6 as 0.34, f m, CYP3A4 as 0.37, and f m, CYP2B6 as 0.08 after intravenous administration of tramadol to optimize the clearance parameters.…”
Section: Methodsmentioning
confidence: 99%
“…A two-fold error range was considered acceptable for model verification as reported previously. 13,14,23,43 The average fold error (AFE) and root mean square error (RMSE) were calculated for further verification of the developed PBPK model. 14,44 The box-whisker plots were used to express the drug dosing recommendations in cirrhosis patients (CP-A-C).…”
Section: Model Appraisal and Verificationmentioning
confidence: 99%
“…Comprehensive physiologically based pharmacokinetic modelling (PBPK) systems have been introduced that replicate the known parameters of the paediatric GI tract to better predict oral dosing [174,175,176,177,178,179,180,181,182]. However, the major limitation in both in vitro and in silico models is the lack of accurate knowledge about the neonatal and infant intestinal parameters [178,183,184].…”
Section: Formulation Considerationsmentioning
confidence: 99%